Depiction of Vishnu at the left end of the Uttaranga - Temples of India Project Team (Jio Institute, 2024)
Vishnu is positioned at the far left end of the uttaranga (entablature) above the lintel of the garbhagriha (sanctum sanctorum). He is depicted holding a gada (mace), a shankha (conch shell), and a chakra (discus). One of his lower hands is gesturing the varadahasta (boon-giving gesture). He is adorned with a kiritamukuta (a cylindrical crown associated with Vaishnava iconography) and various pieces of jewellery.